2022
DOI: 10.3389/fnins.2022.910618
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced effective connectivity from the middle frontal gyrus to the parietal lobe is associated with impaired mental rotation after total sleep deprivation: An electroencephalogram study

Abstract: Sleep deprivation impairs cognitive functions, including attention, memory, and decision-making. Studies on the neuro-electro-physiological mechanisms underlying total sleep deprivation (TSD) that impairs spatial cognition are limited. Based on electroencephalogram (EEG) and Exact Low Resolution Brain Electromagnetic Tomography (eLORETA), this study focused on the effects of TSD on mental rotation and the cognitive neural mechanisms underlying its damage. Twenty-four healthy college students completed mental r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Liu et al found the astronauts showed smaller amplitude of the P300 under the sleep deprivation condition [ 22 ]. In a 36 h sleep deprivation, it s found that the P300 amplitudes decreased, and the cognitive impairment during 38 h of sleep deprivation was mainly in terms of vigilance and reaction time [ 23 ]. Kusztor et al found that 24 h of sleep deprivation resulted in declined sustained attention and reduced P300 amplitudes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al found the astronauts showed smaller amplitude of the P300 under the sleep deprivation condition [ 22 ]. In a 36 h sleep deprivation, it s found that the P300 amplitudes decreased, and the cognitive impairment during 38 h of sleep deprivation was mainly in terms of vigilance and reaction time [ 23 ]. Kusztor et al found that 24 h of sleep deprivation resulted in declined sustained attention and reduced P300 amplitudes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A voxel-based morphometry study showed that the white matter volume of SMG was negatively associated with the PSQI score ( Bai et al, 2022 ), and the higher volume of SMG was correlated with the longer sleep duration ( Cheng et al, 2021 ). Studies found that the increasement in parietal lobe activity could compensate for the decreased cognition caused by insomnia ( Chee and Choo, 2004 ; Li Y. et al, 2022 ). Based on these findings, we believe that acupuncture may relieve cognitive decline caused by insomnia by modulating LC-SMG FC.…”
Section: Discussionmentioning
confidence: 99%
“…EEG data were recorded using a 32-channel EEG recording and analysis system (NeuroScan, Charlotte, NC, USA), which has been extensively used ( accessed on 25 October 2022.) [ 32 , 33 , 34 ]. The installation electrode refers to the international 10–20 system of electrode placement.…”
Section: Methodsmentioning
confidence: 99%